Pengaruh Candi Muaro Jambi Terhadap Pola Pikir Pedagang Desa Sebapo, Kabupaten Muaro Jambi - sam sud din; Santi Hendrayani (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2020)
Muaro Jambi Temple is a tourist attraction that has its own uniqueness and historical heritage that still exists in Jambi Province, although previously it was not separated from the restoration process. As time goes on, more and more traders in the tourist area of Muaro Jambi Temple where there are changes, have a broad influence on the mindset of the people of Sebapo Village. The effect of the environmental conditions of the temple can change the mindset of the community in several ways, the economic, social and cultural conditions of the surrounding communities in the tourist area. especially the residents of Sebapo village. This study aims: 1) to determine the effect of the existence of Muaro Jambi Temple on merchant behavior, 2) to determine the change in the mindset of traders in Sebapo village with the existence of Muaro Jambi Temple. This research use desciptive qualitative approach. The subjects used in the study were members of the Sebo village community, because most of the people depend on their income in Muaro Jambi Temple. Data collection techniques used are direct observation, interviews, and documentation. The data analysis technique used in this study is a qualitative descriptive analysis of the interactive model. Based on the results of the study, it can be concluded that: 1) The social influence of the existence of Muaro Jambi temple on the Sebapo village community, namely: a) the influence of a mindset that causes good social interaction between traders and traders, traders with park managers and traders with tourists through two the process of social contact and social communication and b) the existence of the temple tourism object is used by the community to open as wide a business as possible to create jobs that absorb a lot of labor so as to reduce unemployment, 2) the influence of the existence of the Muaro Jambi temple on the Sebapo village community, namely: a ) the expansion of business opportunities, b) changing the behavior patterns of the community to open jobs, c) increasing the economic income of the people around the temple.